For Your Local Eyes Only: Culture-Specific Face Typicality Influences Perceptions of Trustworthiness. (August 2017) - Sofer, Carmel; Dotsch, Ron; Oikawa, Masanori; Oikawa, Haruka; Wigboldus, Daniel H. J.; Todorov, Alexander
Recent findings show that typical faces are judged as more trustworthy than atypical faces. However, it is not clear whether employment of typicality cues in trustworthiness judgment happens across cultures and if these cues are culture specific. In two studies, conducted in Japan and Israel, participants judged trustworthiness and attractiveness of faces. In Study 1, faces varied along a cross-cultural dimension ranging from a Japanese to an Israeli typical face. Own-culture typical faces were perceived as more trustworthy than other-culture typical faces, suggesting that people in both cultures employ typicality cues when judging trustworthiness, but that the cues, indicative of typicality, are culture dependent. Because perceivers may be less familiar with other-culture typicality cues, Study 2 tested the extent to which they rely on available facial information other than typicality, when judging other-culture faces. In Study 2, Japanese and Israeli faces varied from either Japanese or Israeli attractive to unattractive with the respective typical face at the midpoint. For own-culture faces, trustworthiness judgments peaked around own-culture typical face. However, when judging other-culture faces, both cultures also employed attractiveness cues, but this effect was more apparent for Japanese participants. Our findings highlight the importance of culture when considering the effect of typicality on trustworthiness judgments.